Unleashing potential: a deep dive into AI-blockchain integration for UAV-enhanced tele-surgery - Punitha S.; Preetha K. S. (Cogent Engineering)
The emergence of telemedicine, which allows for distant surgical operations, has significantly changed how medical professionals operate. The most vital application of telemedicine systems, telesurgery, was made possible by the development of telemedicine, which made it easier to monitor sufferers remotely. This study employs qualitative analysis to explore the integration of artificial intelligence (AI) and blockchain technology in UAV-enhanced tele-surgery. Through in-depth interviews and case studies, many researchers investigate the experiences and perceptions of healthcare professionals and patients involved in various innovative approaches. The analysis reveals key themes for improved surgical outcomes, enhanced data security, and the ethical considerations surrounding patient privacy. This work highlights the transformative impact of AI-driven analytics on surgical precision and decision-making, while blockchain's decentralized framework fosters trust and accountability. Pilot studies with simulated surgeries revealed a 25% increase in procedural success rates compared to traditional tele-surgery methods. Challenges such as technological accessibility and comprehensive training are also discussed. Potential benefits include increased accessibility to surgical care in remote areas, enhanced patient safety, and reduced healthcare costs. This research provides future applications in emergency medicine, disaster response, and remote healthcare delivery, highlighting the transformative potential of combining AI and blockchain in the field of tele-surgery.